MORPHOLOGY OF ANEURISMS OF THE ABDOMINAL AORTA´S INFRA-RENAL SEGMENT - Reginato, Gabriela de Souza (2014)
The morphology of aneurisms of the abdominal section of the aorta, at the infra-renal segment, is investigated by a review of the literature. The abdominal section of the infra-renal aorta measures normally between 2 and 2.3 cm in diameter on average. Aneurism occurs when the diameter is equal or greater than 1.5 times. Aneurism of the abdominal segment of the aorta develops slowly and is asymptomatic in most cases, with difficult diagnosis and sudden death. It occurs predominantly in males, in their sixties, and its etiology is polyfactoral with a predominance in atherosclerosis, smoking and arterial hypertension, among other factors. The formation of aneurism is mainly the degeneration of the elastic lamellae that starts on the inner layer and disseminates towards the middle and adventitious ones. Elastin rupture may be seen at the initial stages of swelling. Studies have shown that aneurism of the abdominal aorta is critical when the diameter is greater than 5.0 cm and culminates in death.